ANALISIS STRATEGI MARKETING BRAMBANG CHIPS BERBASIS MEDIA SOSIAL SEBAGAI POTENSI UTAMA MASYARAKAT - Bali, Muhammad Mushfi El Iq; Hayati, Nur; Mukarromah, Nadifatul; Awliya', Indah Zahrotul; Halisah, St. Nur; Miladiana, Miladiana; Dewi, Agustina (Fakultas Sosial dan Humaniora, 2022)
Shallot farming in Pondok Kelor Village is a potential that has opportunities for farmers in the future. The majority of farmers cultivate their agricultural land by planting shallots as a superior crop which gives high expectations from their agricultural business. However, farmers have not been able to maximize the sale of their agricultural products due to the lack of marketing strategies and the development of innovative shallot processing that has attractiveness and selling value. With the right marketing strategy and innovation of processed shallots, it will contribute additional income to farmers in meeting their daily needs as well as initial capital in starting the post-harvest planting season. Based on these assets and potentials, it is necessary to have innovations and marketing strategies from processing shallot agricultural products to increase onion yields. Processed products made are chips from shallots. Marketing strategy is one way to win a sustainable competitive advantage to produce goods or services. Marketing strategy can be seen as one of the bases used in planning a manufacturer as a whole. Given the breadth of the problems that exist within the company, it is necessary to have a comprehensive plan to serve as a guideline for the company's segments in carrying out their activities.